Medical care of acute myocardial infarction patients in a resource limiting country, Trinidad: a cross-sectional retrospective study - Mandreker Bahall; Terrence Seemungal; Katija Khan; George Legall (BMC, 2019)
Abstract Background Cardiovascular disease remains the most common cause of death. However, effective and timely secondary care contributes to improved quality of life, decreased morbidity and mortality. This study analyzed the medical care of patients in a resource limiting country with a first presentation of acute myocardial infarction (AMI). Methods A cross-sectional retrospective study was conducted on first time AMI patients admitted between March 1st 2011 and March 31st 2015 to the only tertiary public hospital in a resource limiting country, Trinidad. Relevant data were obtained from all confirmed AMI patients. Results Data were obtained from 1106 AMI patients who were predominantly male and of Indo Trinidadian descent. Emergency treatment included aspirin (97.2%), clopidogrel (97.2%), heparin (81.3%) and thrombolysis (70.5% of 505 patients with ST elevation MI), but none of the patients had primary angioplasty. Thrombolysis was higher among younger patients and in men. There were no differences in age, sex, and ethnicity in all other treatments. Of the 360 patients with recorded times, 41.1% arrived at the hospital within 4 h. The proportion of patients receiving thrombolysis (door to needle time) within 30 min was 57.5%. In-patient treatment medication included: aspirin (87.1%), clopidogrel (87.2%), beta blockers (76.5%), ACEI (72.9%), heparin (80.6%), and simvastatin (82.5%). Documentation of risk stratification, use of angiogram and surgical intervention, initiation of cardiac rehabilitation (CR), and information on behavioral changes were rare. Electrocardiogram (ECG) and cardiac enzyme tests were universally performed, while echocardiogram was performed in 57.1% of patients and exercise stress test was performed occasionally. Discharge treatment was limited to medication and referrals for investigations. Few patients were given lifestyle and activity advice and referred for CR. The in-hospital death rate was 6.5%. There was a significantly higher relative risk of in-hospital death for non-use of aspirin, clopidogrel, simvastatin, beta blockers, and heparin, but not ACE inhibitors and nitrates. Conclusions Medication usage was high among AMI patients. However, there was very minimal use of non-pharmacological measures. No differences were found in prescribed medication by age, sex, or ethnicity, with the exception of thrombolysis.